Tingkat Kesiapan Venue MICE Di Era New Normal COVID-19 (Stusi Kasus DKI Jakarta) - YOSI ERFINDA; ZETA NOOR FALAH (Journal of Event, Travel and Tour Management, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by SARS-CoV-2 Virus. In Beginning of 2020, World Health Organization has declared as Pandemic all around the world. It has paralysed economic activities which include Meeting, Incentive, Convention and Exhibition and forced all governments in the world, including Indonesia set a policy of controlling and preventing COVID-19.This policy force of the activity New Normal in Indonesia. Based on statement by Ministry of Tourism and Economic Creative in 2020 there some 84,8% MICE activities in Indonesia was cancelled. Ministry of tourism and economic creative made policy for reduce impact of pandemic through Cleanliness, Health, Safety and Environmental Sustainability for MICE. DKI Jakarta is the object of this research. The researcher can collected 38 respondens of Venue in DKI Jakarta such as Hotel, Convention Center, Resort and Apartement used online survey. Research Methodology use GAP Analysis to compare between the application of health protocol that done by Venue MICE or against a standard applied in guidance of CHSE for MICE in Indonesia. There are 8(eight) criteria in guidance of CHSE for MICE. The research result showed that 1(one) criteria is food and beverages providers fulfilled the achievements 100% . And for 7(seven) criteria in positions of 75% - < 100% it means the current of Venue MICE in the standard assessment result with the standard applied in guidance CHSE is will fulfilled. This should served as reference Venue MICE in DKI Jakarta can organize MICE activities in Era of New Normal.